Invasive Pulmonary Aspergillosis Diagnosis via Peripheral Blood Metagenomic Next-Generation Sequencing - Ma, Xiaoxu; Zhang, Suping; Xing, Haizhou; Li, Huiling; Chen, Jiajun; Li, Haijun; Jiao, Mengfan; Shi, Qingmiao; Xu, Aiguo; Xing, Lihua; Cao, Weijie (Frontiers in Medicine, 2022)
Invasive pulmonary aspergillosis (IPA) is one of the major causes of morbidity and mortality in immunocompromised patients such as hematological malignancies, hematopoietic stem cell transplantation and solid organ transplantation. The diagnosis of IPA in these patients is still difficult because it has no obvious specificity in clinical symptoms, signs and imaging, and test sensitivity of blood 1,3-β-D-glucan test, galactomannan are low. Therefore, we still need to explore more diagnostic methods. In our study, via peripheral blood metagenomic next-generation sequencing (mNGS), five patients were tested positive for Aspergillus DNA and then quickly diagonised as invasive pulmonary aspergillosis (IPA). Out of the 5 cases, 1 was proven and 4 were probable IPA. The underlying diseases of the 5 patients were myelodysplastic syndrome (2 cases), acute myeloid leukemia (2 cases) and renal transplantation (1 case). Then they were diagnosed as IPA by other methods such as lung histopathology, bronchoalveolar lavage fluid (BALF) mNGS and sputum culture or sputum mNGS. In case 1, sputum culture suggested Aspergillus flavus. In case 2, both Grocott methenamine silver (GMS) stain of lung histopathology and lung tissue mNGS suggested Aspergillus infection. In case 3 and 4, BALF-mNGS suggested Aspergillus infection. In case 5, sputum mNGS suggested Aspergillus infection. In conclusion, detecting the cfDNA of Aspergillus via peripheral blood mNGS can be applied to diagnose IPA and is a rapid and non-invasive diagnosis method.